Statistical behaviours and forecast of cash Waqf collection - Azrai Azaimi Ambrose, Azniza Hartini; Abdullah Asuhaimi, Fadhilah (IIUM Institute of Islamic Banking and Finance (IIiBF), International Islamic University Malaysia, 2022)
The main purpose of this research is to elucidate the efficacy of statistical measurements on cash waqf collection. To demonstrate this, the sub-objectives of this study are (1) to examine the statistical behaviours of cash waqf and (2) to ascertain future cash waqf collection trend. Numerical measures were used to describe statistical behaviours of cash waqf while Box-Jenkins methodology was employed for forecasting. Cash waqf data of State Islamic Religious Council (SIRC) of Pulau Pinang and Perbadanan Wakaf Selangor (PWS) had been collected to address these sub-objectives. During the period of study, it was found that cash waqf collected by SIRC of Pulau Pinang was more predictable than PWS even though PWS collected higher value on average. As such, the statistical measurements had identified different cash waqf management strengths. This is hoped to encourage cross-sharing exercises between SIRCs so cash waqf management can continuously be improved. Furthermore, the tentative sum of cash waqf collection forecasted using time series forecasting shows that cash waqf managers can make informed decision for the beneficiaries’ best interest. The usefulness of statistical measurements elucidated above is hoped to convince cash waqf managers to make cash waqf data readily accessible. This paper fills the gap in the literature of cash waqf collection statistics which is extremely limited. This paper is expected to be an impetus for future studies on advanced cash waqf statistics that could add relevance of waqf to the modern economy.